2013 IEEE Energy Conversion Congress and Exposition 2013
DOI: 10.1109/ecce.2013.6647163
|View full text |Cite
|
Sign up to set email alerts
|

Rotor impedance of the high frequency circulating bearing current path in inverter-fed AC machines

Abstract: The circulating bearing current depends on the common mode stator ground current and the stator laminated core impedance, but also on the bearing impedances and on the rotor impedance of the circulating bearing current path. In the literature, the rotor impedance was neglected, or it was considered as a small air gap and end-winding cavity inductance. It is shown here by calculation and measurement that the rotor impedance is not negligible, and it is much larger than the air gap and end-winding cavity inducta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…To avoid the damage patterns introduced by the bearing currents mentioned, suitable prevention mechanisms for the drive system, consisting of the inverter, the machine, and the gearbox, must be selected in the design stage. For this purpose, various approaches to predicting bearing currents have been developed, which are mostly limited to an electrical machine [25,31,32]. If only the rolling bearing is considered, the use of hybrid bearings seems to be a suitable countermeasure to solve harmful bearing currents [33].…”
Section: System Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…To avoid the damage patterns introduced by the bearing currents mentioned, suitable prevention mechanisms for the drive system, consisting of the inverter, the machine, and the gearbox, must be selected in the design stage. For this purpose, various approaches to predicting bearing currents have been developed, which are mostly limited to an electrical machine [25,31,32]. If only the rolling bearing is considered, the use of hybrid bearings seems to be a suitable countermeasure to solve harmful bearing currents [33].…”
Section: System Modelingmentioning
confidence: 99%
“…First efforts were made with lumped parameter models for the high-frequency behavior prediction of an electrical machine, as given in [35,36], but they are useless for prediction in the design stage because the identification of the parameters in the proposed equivalent circuit is based on measurements. Further, multi-conductor-transmission line models, such as those presented in [30,32,[37][38][39], are widely accepted for modeling high-frequency machine behavior. According to the multi-conductor-transmission line, a conductor i coupled with a conductor j is modeled, as shown in Figure 8, by a self-resistance R ii , a self-inductance L ii , a capacitance C g to ground, a capacitance C k to conductor j, and a resistance R g and resistance R CM representing dielectric losses, which are usually neglected.…”
Section: Electrical Machine Modelmentioning
confidence: 99%
“…In a study reported in [74] the common mode flux was calculated by 2D axisymmetric FEM and combined with an analytical method. It was demonstrated that the rotor impedance cannot be neglected at high frequency as it is often comparable to the stator impedance.…”
Section: Finite Element Calculation Of đť’Š đť‘Şđť‘©mentioning
confidence: 99%
“…fit relative error 1 averaged over all frequencies and currents for different optimization methods. 1 see formula (4), 2 the PSO error is unacceptable. for higher values of currents i ≥ 30 A (see Fig.…”
Section: Langevin Function For Nonlinearity Modellingmentioning
confidence: 99%